Peran Peran aktor Twitter pada gerakan tagar #unsubscribepodcastcorbuzier - Yumna Khairunnisa; Aulia, Tazkya; Ompusunggu, Esra Julianti; Charisma, Thia (Faculty of Communications Science, Dr. Soetomo University, 2022)
The #CloseTheDoor Corbuzier Podcast caused controversy by uploading content featuring LGBT (Lesbian, Gay, Bisexual, and Transgender). As a form of rejection, the public used the hashtag #UnsubscribePodcastCorbuzier on Twitter to spawn a New Social Movement. The research reveals the question of how the Twitter actor role is formed by the hashtag communication network #UnsubscribePodcastCorbuzier. This study uses qualitative Social Network Analysis and Graph Theory. Based on network system analysis, @youtube became a very striking actor in the network. Relation has the property of the direction of the relationship or directed graph. Based on the results of the actor centrality research, YouTube actors in this study have high centrality. The #UnsubscribePodcastCorbuzier hashtag movement aligns with Jenkins' theory of Participatory Media Culture. People connect with each other through social media, sharing thoughts and tagging other accounts related to specific topics discussed.